(untitled) (Journal of the College of Basic Education, 2025)
Omission from history is one of the challenges facing historians and intellectuals in their attempts to present a comprehensive and accurate historical narrative that shows all the parts and positions. It may be intentional by a certain group that had control at a certain time, or unintentional due to lack of information. Due to the importance of all individuals involved in the Karbala incident, the research included three topics: The first topic: We addressed the linguistic and technical aspects of absentations . In the second topic: We addressed the Karbala incident between the present and the past. In the third topic: The subject of those absent in the Karbala incident came.